1997
DOI: 10.1002/hep.510260601
|View full text |Cite
|
Sign up to set email alerts
|

Blunted responsiveness of the neuronal activation marker Fos in brainstem cardiovascular nuclei of cirrhotic rats

Abstract: Cardiovascular function in cirrhosis is deranged, with indirect evidence of abnormal central cardiovascular regulation. We aimed to elucidate the role of brainstem cardiovascular nuclei in hemodynamic regulation by examining the protein product, Fos, of the immediate-early gene c-fos, in cirrhotic rats. Cirrhosis was induced by chronic bile duct ligation (BDL) of 25-days duration, while controls underwent a sham operation. To examine the effects of jaundice per se in the absence of cirrhosis, a third group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…25 However, accumulating evidence suggests that central nervous regulatory mechanisms are abnormal in liver disease. [26][27][28] Our previous study showed that baseline Fos expression in the NTS and VLM were significantly increased, but neuronal activation responses to both hemorrhage and volume expansion were severely blunted in cirrhotic rats. 28 This finding implies that at least part of the vascular hyporesponsiveness to constrictor or dilator influences might be secondary to attenuated central cardiovascular control mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…25 However, accumulating evidence suggests that central nervous regulatory mechanisms are abnormal in liver disease. [26][27][28] Our previous study showed that baseline Fos expression in the NTS and VLM were significantly increased, but neuronal activation responses to both hemorrhage and volume expansion were severely blunted in cirrhotic rats. 28 This finding implies that at least part of the vascular hyporesponsiveness to constrictor or dilator influences might be secondary to attenuated central cardiovascular control mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…Chronic bile duct ligation (BDL), a commonly used animal model of obstructive cirrhosis, is associated with elevated circulating vasopressin, cytokines, and activation of the renin-angiotensin system (33, 3740). In this model, TRPV4 protein content is increased in the SON as is its expression in lipid rafts within the hypothalamus (41).…”
Section: Introductionmentioning
confidence: 99%
“…In the CNS, neurons that have been activated show nuclear Fos (the protein product of the immediate‐early gene c‐fos ) staining by immunohistochemistry. Lee's lab has demonstrated that neurons in the CV‐regulatory nuclei listed above show persistent activation in portal hypertensive and cirrhotic rats .…”
mentioning
confidence: 99%